A Review on Impact of Organisational Culture and Work Motivation on Employee’s Performance - Mubintaj, Morageri; Prince James S Bangera; Deepika Ravi (Gayaku Publisher, 2024)
Organization culture and environment and work motivation plays vital role on employees’ performance. This study examines to analyze and comprehend how an organization's culture and environment affect workers' attitudes, behaviours, output, and motivation for their jobs. Using a structured review of prior research of existing research, it explores the multifaceted impact of organizational culture on employees within various workplace contexts. The review examines the ways in which organizational values, norms, and leadership styles shape employee engagement, motivation, and satisfaction. It investigates the influence of a positive organizational culture on teamwork, innovation, and overall productivity. Additionally, the article explores the challenges posed by cultural mismatches and discusses strategies for fostering a supportive and empowering work. Synthesizing diverse perspectives, the paper offers and empirical findings, this review presents actionable insights for organizations aiming to cultivate a conducive work environment that enhances employee well-being and maximizes performance outcomes.